Determining the role of STAT1 and STAT3 transcription factors in transcriptional memory - Seyed Hassan Tehrani, Sahar (2022)
"Transcriptional memory is a cellular phenomenon where an environmental stimulus triggers a heritable primed state that results in an enhanced secondary response once cells are reexposed to the stimulus. Such phenomenon has been observed not only in immune cells but also in non-immune cells as well as in different model organisms such as fruit fly, yeast and human to enable them to respond faster to different environmental and physiological conditions and recurrent stresses. "